Access to land and land rights in post conflict societies in Uganda : a perspective on women's and children's rights - Akonumbo, Atangcho Nji (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.